Specific Nucleic AcId Ligation for the detection of Schistosomes: SNAILS - Webb, Alexander James; Allan, Fiona; Kelwick, Richard J. R.; Beshah, Feleke Zewge; Kinung’hi, Safari Methusela; Templeton, Michael R.; Emery, Aidan Mark; Freemont, Paul S. (PLOS Neglected Tropical Diseases, 2022)
Author summary Schistosomiasis is a neglected tropical disease, caused by the parasitic trematodes of the genus Schistosoma. Schistosomiasis is endemic to regions within Africa, Asia and South America with at least 250 million people infected and a further 779 million at risk of infection. The lifecycle of schistosomes are complex and involve specific freshwater intermediate snail hosts which shed infective cercariae into the waterbodies they inhabit. Schistosomiasis is subsequently transmitted to humans or animals that contact cercariae contaminated water. In Africa, human disease is largely caused by Schistosoma mansoni and Schistosoma haematobium. However, endemic regions also typically feature animal-infecting schistosomes that can have broader economic and/or food security implications. Therefore, the development of species-specific Schistosoma detection technologies may help to inform local environmental, food security and health programmes. To this end, we re-purposed a nucleic acid detection technology to enable the detection of different schistosome species. Our DNA-biosensor, abbreviated as ‘SNAILS’, employs carefully designed probes that recognise species-specific DNA sequences, coupled with enzymatic amplification steps, and a fluorescent signal-dye to indicate a positive detection. ‘SNAILS’ successfully differentiates between S. mansoni and S. haematobium samples and could conceivably be employed within future global health programmes.